2016
DOI: 10.2147/dddt.s103894
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-unit tablet of probiotic bacteria for improved storage stability, acid tolerability, and in vivo intestinal protective effect

Abstract: The aim of this study was to formulate probiotics-loaded pellets in a tablet form to improve storage stability, acid tolerability, and in vivo intestinal protective effect. Bacteria-loaded pellets primarily prepared with hydroxypropyl methylcellulose acetate succinate were compressed into tablets with highly compressible excipients and optimized for flow properties, hardness, and disintegration time. The optimized probiotic tablet consisted of enteric-coated pellets (335 mg), microcrystalline cellulose (Avicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This tablet was able to provide bacterial viability for 6 months at room conditions and was able to withstand ambient conditions better than uncoated strains. It was also found that the tablets exhibited sufficient tablet hardness and disintegration time [80].…”
Section: Different Approaches To Oral Pharmabiotic Tabletsmentioning
confidence: 88%
“…This tablet was able to provide bacterial viability for 6 months at room conditions and was able to withstand ambient conditions better than uncoated strains. It was also found that the tablets exhibited sufficient tablet hardness and disintegration time [80].…”
Section: Different Approaches To Oral Pharmabiotic Tabletsmentioning
confidence: 88%
“…Probiotics are used as a premix in admixture with animal feed. Probiotic cultures are exposed to external effects not only during the preparation of feed but also during the application of compositions, which result in a further reduction in the number of germs [2,3]. When introduced into the digestive tract, probiotic bacteria are exposed to the acidic action of gastric juice and bile acids that reduce the viability of bacterial cells [4][5][6].…”
Section: Introductionmentioning
confidence: 99%